The Connection Between ESG Evaluation and Financial Performance: A Study of European Businesses - Dimitriou, Nikolaos (My University, 2023)
Background Customers, members of society, and top executives are all showing a growing interest in sustainable practices. Opportunities for leadership in areas of long-term corporate social responsibility and financial success are becoming more available to businesses as they shift towards a more sustainable company model. Objectives The goal of this dissertation is to analyze/evaluate the connection between a company's ESG assessment/evaluation/scoring, and its bottom line in terms of financial performance. European businesses are the focus of the research. An ancillary goal is to look at other industries to see whether there are any differences in the nature of this connection between firms and their respective sectors. Method To support its claims, the dissertation draws on secondary data collected for multiple companies between 2009 and 2020. The data was designed as panel data so that it could be used to study several entities across this time frame. Panel regressions were used to probe the motivation for the study. Results When companies across all industries are combined into a single dataset, it becomes clear that the Environmental scoring/rate has a substantial influence on earnings. The correlation between ESG and financial success is typically negative, as seen by the industries with the highest ESG ratings. Conclusion This dissertation adds to the body of research concerning environmental, social, and financial performance. Consumers, financiers, and business tycoons can all benefit from current and future research's insights as they consider how they can adopt more ethical practices. The link between all ESG factors and a company's net income/profitability is an intriguing area for further study in Europe.
Keywords: ESG Evaluation; Financial Performance; European Businesses